Socio-Economic Impact of Rubber Business on Latex Tappers in Ijebu Waterside Local Government Area of Ogun State, Nigeria - O. C. Odeyale; E. B. Olawuyi; F. F. Ojo-Fakuade; A. S. Adetunji (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to investigate the socio-economic impact of rubber business on latex tappers in Ijebu Waterside Local Government Area of Ogun State, Nigeria using appropriate standard methods The result showed that all the tappers are male, (35.0%) of the respondents are in their 40s, 55.0% are married and 66.0% had secondary school education. Furthermore, all (100.0%) the tappers went through training for a minimum of three months before starting the business and they all admitted that rubber tree lasts for 30yrs and that the shelf life of rubber product is one year. Most (67.0%) claimed that rubber tapping business was moderately profitable and that it has helped improve their standard of living. 92.0% claimed that the cost of maintaining the business was moderate and that the business has a significant impact on the community because it serves as a source of employment to residents and helped to alleviate poverty in the study area. Among the challenges experienced by rubber tappers, insecurity and theft of rubber product stood out as a principal challenge. The study therefore recommends that adequate security should be provided either by the associations they form or by government in order to maximize their profit from the business.